The Power of Energy Justice & the Social Contract - Heffron, Raphael J.; de Fontenelle, Louis (Just Transitions, 2024)
This open access book focuses on the energy sector and will make a significant contribution to its continued evolution. For many years, the energy sector has been missing a raison d'etre and now finally there are increased calls for that to be justice. Hence, this book will develop the concept of energy justice and how it needs to be formalised in a new 'social contract' with all stakeholders in society. The focus will be on improving legal systems at local, national and international levels while ensuring that justice is a core issue within energy law, the legal system and more broadly in society.